ChemInform Abstract: Mild C—H/C—C Activation by Z‐Selective Cobalt Catalysis. Issue 44 (13th October 2016) - Zell, Daniel; Bu, Qingqing; Feldt, Milica; Ackermann, Lutz
Abstract: The cobalt‐catalyzed reaction of indoles (I) with vinylcyclopropanes (II) leads to desired 2‐functionalized indoles with moderate to high Z‐selectivity.